Exploring mobile learning in the Third Space. Issue 2 (15th March 2017) - Schuck, Sandy; Kearney, Matthew; Burden, Kevin
Abstract : Mobile learning is enabling educators and students to learn in ways not previously possible. The ways that portable, multi-functional mobile devices can untether the learner from formal institutional learning give scope for learning to be conceptualised in an expanded variety of places, times and ways. In this conceptual article the authors articulate this notion by using the metaphor of the Third Space to envision what can be achieved with mobile learning. They outline their use of the metaphor, consider how it extends notions of twenty-first century learning and use a previously established Mobile Pedagogical Framework to provide a context for the discussion. They conclude with implications of learning in the Third Space for teachers and students. These implications suggest that roles of teachers and students and structure of the curriculum need to change to ensure we leverage the potential of mobile learning.